2013
DOI: 10.1130/g34823.1
|View full text |Cite
|
Sign up to set email alerts
|

Localized tsunamigenic earthquakes inferred from preferential distribution of coastal boulders on the Ryukyu Islands, Japan

Abstract: The occurrence of large earthquakes and tsunamis along the Ryukyu Trench is a subject of continuing interest, the key to which is the long-term geological record. Here we describe the clast size and spatial distributions of ~2900 boulders on the reefs of the Ryukyu Islands, Japan, as markers of paleotsunamis and causative tsunamigenic earthquakes. Boulders of tsunami origin were observed only at a specifi c island group at the southern end, suggesting the local occurrence of tsunamigenic earthquakes there. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…The 1771 tsunami was an extremely large event, but historical documents show that it damaged only a restricted area, the Sakishima Islands, including Ishigaki Island (Goto et al 2010). Based on the clast sizes and spatial distributions of boulders on the reefs of the Ryukyu Islands, Goto et al (2013) suggested that large tsunamis have struck locally but repeatedly around the Sakishima Islands, but not around the Amami and Okinawa Islands, at least during the past 2300 years.…”
Section: Study Areamentioning
confidence: 99%
“…The 1771 tsunami was an extremely large event, but historical documents show that it damaged only a restricted area, the Sakishima Islands, including Ishigaki Island (Goto et al 2010). Based on the clast sizes and spatial distributions of boulders on the reefs of the Ryukyu Islands, Goto et al (2013) suggested that large tsunamis have struck locally but repeatedly around the Sakishima Islands, but not around the Amami and Okinawa Islands, at least during the past 2300 years.…”
Section: Study Areamentioning
confidence: 99%
“…Dawson and Shi 2000). Offshore, the tsunami-derived material is distributed more evenly and occupies broader areas than the sediments deposited by tropical storms (Paris et al 2009;Goto et al 2013). A comparable thickness of the stromatoporoid beds between the sections and a lack of lateral size segregation of the stromatoporoids resemble the above-described modern boulder distribution, governed mainly by sea bottom topography.…”
Section: Stromatoporoid Beds -Distributionmentioning
confidence: 94%
“…Goto et al 2013), which are frequently exposed to both tsunami waves and tropical storms. Boulders of tsunami origin were transported there over a distance of more than 1 km landward from the reef crest, whereas the occurrence of those deposited by hurricanes is limited to a narrow strip (~ 200m) on the leeward side of the reef (Goto et al 2010a).…”
Section: Stromatoporoid Beds -Distributionmentioning
confidence: 99%
“…The vastness of the area covered by the parabiostromal beds and the lack of stromatoporoid lateral size segregation resembles the distribution of modern tsunami-derived material and differs from storm derived deposits (comp. Paris et al 2009;Goto et al 2007Goto et al , 2013. The material was transported both by traction by the oncoming tsunami waves (clast supported varieties), and from suspension, probably during backwash flows (bioclastic limestones with the material derived from shallow-water areas) (comp.…”
Section: Tsunami Interpretation Of Stromato-poroid Beds and Flat-pebbmentioning
confidence: 99%